Development and characteristics of a tourist visit in Ljubljana from 1960 - Horvat, Uroš (Journal for Geography, 2019)
The author points out the main periods of tourist development in Ljubljana after 1960, using the data of a tourist visit (the number of tourists and overnight stays, the average length of stay of tourists, their nationality, the seasonality of the tourist visit, the distribution by type of accommodation). He emphasizes the importance of changes of the tourist flows during the time. Ljubljana has become the most important tourist destination in Slovenia by number of overnight stays, as it has overtaken other tourist destinations in recent years with an extremely increased tourist visit. With its location and tourist offer, it is especially suitable for the so-called "short city break" and as a starting point for exploring other parts of Slovenia. The promotion of this type of tourism is influenced by the proximity of the airport and the providers of the sharing economy (accommodation, transport), which especially attract tourists who want a shorter vacation, exploring new lands and cultures or just having fun.